(untitled) (TEST Ticontre. Theory Text Translation, 2023)
The oft quoted and much discussed conclusion of Canto 81 in the Pisan Cantos – a landmark work of poetic Modernism – sealed an unlikely "pact" between Ezra Pound and Pier Paolo Pasolini during an interview for Italian television recorded in 1967. With this meaningful encounter as its starting point, my study retraces the complex paths followed by Pound’s text; frequently de-contextualized and simplified, it has undergone multiple procedures of interlingual and intersemiotic translation, acquiring a variety of new functions and meanings.